The Art of Learning: Developing a growth mindset - Gomez, Leonardo (CIEX JOURNAL, 2017)
Are people born intelligent? Is intelligence fixed, or can it be improved? Why do so many students have very shallow levels of learning and comprehension? Why do so many people start learning a foreign language but end giving up? In this session, we will answer these questions and learn about what a “growth mindset“ is, why it is important, and how it can have a long-lasting impact on the way we teach and learn in the classroom.